Acupuncture as Treatment for Female Infertility: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (16th February 2022) - Quan, Kewei; Yu, Chuyi; Wen, Xiaohui; Lin, Qiuping; Wang, Naiping; Ma, Hongxia
Abstract : Background . The effects of acupuncture on female infertility remain controversial. Also, the variation in the participant, interventions, outcomes studied, and trial design may relate to the efficacy of adjuvant acupuncture. The aim of the study is to systematically evaluate the efficacy and safety of acupuncture for female with infertility and hopefully provide reliable guidance for clinicians and patients. Methods . We searched digital databases for relevant studies, including EMBASE, PubMed, Cochrane Library, and Web of Science, and the Cochrane Library up to April 2021, for randomized controlled trials (RCTs) evaluating the effects of acupuncture on women undergoing IVF and other treatment. We included studies with intervention groups using acupuncture and control groups consisting of no acupuncture or sham (placebo) acupuncture. Primary outcomes were clinical pregnancy rate (CPR) and live birth rate (LBR). Meta-regression and subgroup analysis were conducted on the basis of ten prespecified covariates to investigate the variances of the effects of adjuvant acupuncture on pregnancy rates and the sources of heterogeneity. Results: Twenty-seven studies with 7676 participants were included. The results showed that the intervention group contributes more in outcomes including live birth rate (RR = 1.34; 95% CI (1.07, 1.67); P < 0.05 ), clinical pregnancy rate (RR = 1.43; 95% CI (1.21, 1.69); P < 0.05 ), biochemical pregnancy rate (RR = 1.42; 95% CI (1.05, 1.91); P < 0.05 ), ongoing pregnancy rate (RR = 1.25; 95% CI (0.88, 1.79); P < 0.05 ), adverse events (RR = 1.65; 95% CI (1.15, 2.36); P < 0.05 ), and implantation rate (MD = 1.19; 95% CI (1.07, 1.33); P < 0.05 ) when compared with the control group, and the difference is statistically significant. In terms of the number of oocytes retrieved, good-quality embryo rate, miscarriages, and ectopic pregnancy rate, the difference between the acupuncture group and the control group was not statistically significant. Conclusions: Our analysis finds a benefit of acupuncture for outcomes in women with infertility, and the number of acupuncture treatments is a potential influential factor. Given the poor reporting and methodological flaws of existing studies, studies with larger scales and better methodologies are needed to verify these findings. More double-blind RCTs equipped with high quality and large samples are expected for the improvement of the level of evidence.